Get Capone : the secret plot that captured America's most wanted gangster - Eig, Jonathan (Simon & Schuster, 2010)
Drawing on thousands of pages of recently discovered government documents, wiretap transcripts, and Al Capone's handwritten personal letters, "New York Times" bestselling author Jonathan Eig tells the dramatic story of the rise and fall of the nation's most notorious criminal in rich new detail.